2020
DOI: 10.14715/cmb/2020.66.7.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dendrobium polysaccharides on human brain microvascular endothelial cell injury induced by ox-LDL via regulating the miR-378 expression

Abstract: Brain microvascular endothelial cells are a key part of the blood-brain barrier. This experiment was set up to investigate the effect and molecular mechanism of Dendrobium polysaccharide on oxidized low-density lipoprotein (ox-LDL)-induced damage to the human brain microvascular endothelial cells.For this purpose, human brain microvascular endothelial cells HBMEC were divided into control group (without any treatment), ox-LDL group (50 μg/mL ox-LDL), Dendrobium polysaccharide low, medium and high concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that DOP suppresses inflammation and oxidative stress in mice with colitis 9 and ox-LDL-induced oxidative stress and apoptosis in human brain microvascular endothelial cells. 29 Given that both inflammation and apoptosis play an important role in vascular calcification, 16,17,30 it was speculated that DOP may inhibit vascular calcification. Interestingly, we found that DOP treatment inhibited the calcification of rat VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that DOP suppresses inflammation and oxidative stress in mice with colitis 9 and ox-LDL-induced oxidative stress and apoptosis in human brain microvascular endothelial cells. 29 Given that both inflammation and apoptosis play an important role in vascular calcification, 16,17,30 it was speculated that DOP may inhibit vascular calcification. Interestingly, we found that DOP treatment inhibited the calcification of rat VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…PDC is one of the main active ingredients of Dendrobium candidum and has good anti-inflammatory, antioxidant, and other biological activities [10,[21][22][23]. Different concentrations of PDC have been identified by Chen et al to incresease the activity of SOD, which could contribute to inhibiting oxidative stress and apoptosis of human brain microvascular endothelial cells [24]. The results of this experimental study found that the intracellular ROS level increased significantly, and the activity of SOD in the culture medium decreased under high glucose culture, confirming once again the role of high glucose in oxidative damage and influencing endothelial cell proliferation during incubation with endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral infarction is also known as ischemic stroke, as it is called stroke in traditional Chinese medicine. It is a blood supply disorder in the local brain tissue area caused by various reasons, leading to ischemic and hypoxic necrosis of brain tissue, and then resulting in corresponding neurological deficits clinically (1)(2)(3). Cerebral infarction is classified into cerebral thrombosis, cerebral embolism, and lacunar cerebral infarction according to the different pathogeneses.…”
Section: Introductionmentioning
confidence: 99%